Refraction of coefficient, density and polarizability сryovacuum condensate of methane - Shinbayeva, A.K.; Drobyshev, A.S.; Ramos, M.; Sokolov, D.Yu. (Recent Contributions to Physics, 2018)
It is proposed to discuss the experimental setup, measurements of methods and preliminary results of the research dependence of the properties of condensates cryovacuum methane and conditions of condensation. The main parameters of the experimental complex characterized by the following parameters: temperature of the condensation surface in the range of T = 12 K and T = 200 K; the pressure in the vacuum chamber of 10-8 Torr to 1000 Torr; film thickness of cryocondensate from 0.5 microns to 100 microns. Measurements of refractive coefficient, the thickness and density cryocondensates carried out using a two-beam laser interferometer at a wavelength of 630 nm. IR spectrums of these samples were measured by X-upgraded spectrometer 29 in the frequency range 400 cm-1 to 4200 cm-1. The data obtained on the dependence of the refractive coefficients of the methane condensing temperature leads to the conclusion that in the vicinity of α-β-transition at T = 20.4 K this dependency undergoes abrupt discontinuity.